2019
DOI: 10.1042/bsr20190288
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for distant metastasis of patients with primary triple-negative breast cancer

Abstract: Objective: Triple-negative breast cancer (TNBC) involves higher rates of recurrence and distant metastasis. The present study sought to characterize the risk factors for distant metastasis of TNBC. Methods: The Surveillance, Epidemiology, and End Results (SEER) database was exploited to enroll patients diagnosed with TNBC from 2010 to 2015. The eligible patients were dichotomized into locoregional and distant metastasis at the time of diagnosis. Patients’ demographics and tumor features, and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 17 publications
6
59
0
1
Order By: Relevance
“…However, specific subtypes of breast cancer in our cohort did not show a significant association with the risk of distant metastasis ( Table 5). Several studies have shown a higher risk of distant metastasis in Her-2-enriched [42] and TNBC subtype [43] and a lower risk of distant spread in the luminal subtype [42]. In this study, we showed specific risk factors of distant metastasis in luminal A-subtype, i.e., advanced stages (OR 2.160), tumor infiltration to skin and chest wall (OR 2.685), and positive axillary lymph nodes (OR 2.571).…”
Section: Discussionmentioning
confidence: 99%
“…However, specific subtypes of breast cancer in our cohort did not show a significant association with the risk of distant metastasis ( Table 5). Several studies have shown a higher risk of distant metastasis in Her-2-enriched [42] and TNBC subtype [43] and a lower risk of distant spread in the luminal subtype [42]. In this study, we showed specific risk factors of distant metastasis in luminal A-subtype, i.e., advanced stages (OR 2.160), tumor infiltration to skin and chest wall (OR 2.685), and positive axillary lymph nodes (OR 2.571).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of TNBC as the most aggressive form is 10-20%, with higher abundance in the cohort of young women. This molecular subtype is associated with an advanced stage, higher grade of the tumor, overall worse survival rates of patients associated with cancer recurrence, and development of metastasis [24]. Immunohistochemically, TNBC is characterized by the lack of three receptors: estrogen receptor (ER), progesterone receptor (PR), and HER2.…”
Section: Breast Cancer From the View Of Prevalence And Intrinsic Subtmentioning
confidence: 99%
“…Nonetheless, the lack of a targeted therapy and the TNBC heterogeneity highlighted the urgent medical need to identify therapeutic targets and develop novel effective medicines capable to overcome drug resistance in this aggressive BC. A great deal of effort is currently devoted to find out whether certain treatments can interfere with cellular and molecular processes fueling TNBC growth, trying to create new medical therapies able to hinder the typical TNBC metastatic pattern (i.e., frequent occurrence of distant metastases, mainly localized in lung, central nervous system, and bones) often associated with poor prognosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, we exploited the effect of an oral supplementation with "Micotherapy U-care" (M. U-care), a novel medicinal mushroom blend, consisting of a mixture of extracts from the above reported five varieties, in a 4T1 triple-negative mouse BC model. We addressed specific endpoints and pathological outcomes of the murine pulmonary tissue, the lung being one of the distant organs frequently involved in typical metastasis pattern of primary TNBC [7]. We evaluated different markers of general lung toxicity, inflammation, fibrosis, and oxidative stress, both in parenchyma and metastases.…”
Section: Introductionmentioning
confidence: 99%